RESPONSABILIDADE SOCIAL DAS EMPRESAS: CONTROVÉRSIAS E CONSENSOS EM TORNO DA DOAÇÃO AO FUNDO DA INFÂNCIA E DO ADOLESCENTE - Carriço, Fernando Albano (2008)
This research analyses companies donations to the Fund for Children s and Adolescents Rights (Fundo de Direitos da Criança e do Adolescente - FIA) to finance projects exclusively for the protection of children s and adolescents rights, which are established in the Statute of Children and Adolescent (Estatuto da Criança e do Adolescente - ECA). Donations made for this project, previously approved and presented to the Rights Council have provoked controversy over their legality. The research carried out with the prosecutors, judges and lawyers showed extreme positions against direct donations and others completely in favor, all of them with arguments based on sound juridical foundation. A conciliatory position will be necessary because children and adolescent need good projects that meet their demands. To find support for the study it was necessary to raise (1) the question of poverty and social inequality which have challenged successive governments, (2) the role of the Company when practicising its Social Responsibility and (3) the juridical structure that treats children and adolescents as individuals, with the rights and obligations of citizens.